Hospital antibiotic management in the Czech Republic--results of the ABS maturity survey of the ABS International group - Jindrák, Vlastimil; Urbásková, Pavla; Bergerová, Tamara; Buchta, Vladimír; Hanslianová, Markéta; Horníková, Magdaléna; Chmelík, Václav; Nyc, Otakar; Vanis, Václav; Working Group on Monitoring Antimicrobial Resistance (Wiener klinische Wochenschrift, 2008)
BACKGROUND: Hospital antibiotic stewardship (ABS) programs are essential for ensuring long-lasting quality of antibiotic usage and for controlling antimicrobial resistance in the hospital setting. METHODS: A questionnaire for self-assessment of a hospital's ABS maturity was sent to 80 Czech hospitals in May 2007. The survey was focused on diagnostic issues, control of antibiotic consumption, antibiotic-related organization and tools, antibiotic-related personnel development and antibiotic-related relationships to relevant environments. RESULTS: Of 80 addressed hospitals, 45 sent back processed questionnaires (response rate 56.3%). These 80 hospitals cover about 85% of the Czech population. All Czech university hospitals were included in the replying group. The listed diagnostic tools were declared available by all hospitals; 44 of 45 hospitals have surveillance systems for antibiotic resistance rates. Control of antibiotic consumption was available only partially in 42 of 45 hospitals. Some antibiotic tools need to be improved and must be used more frequently. Official recognition, job descriptions and better funding of antibiotic personnel are needed, as well as support for further development of ABS structures and functions. DISCUSSION: The basic structure of ABS is well developed in the Czech hospitals. A network of antibiotic centers focusing their services on optimization of antibiotic usage has been in place in the Czech Republic since the 1970s. Nevertheless, the survey revealed a clear need and many opportunities for further improvement. Control of antibiotic consumption is not implemented in all Czech hospitals and some of the essential antibiotic tools should be used more widely.
Keywords: Hospitals; Bacterial Infections; infekce spojené se zdravotní péčí; Česká republika; antibakteriální látky; Population Surveillance; incidence; průzkumy a dotazníky; Anti-Infective Agents; Czech Republic; bakteriální infekce; lidé; antibiotická rezistence; Anti-Bacterial Agents; Cross Infection; Drug Resistance, Microbial; Humans; epidemický výskyt choroby; surveillance populace; Disease Outbreaks; Surveys and Questionnaires; antiinfekční látky; nemocnice; Incidence